WRITING SKILLS ENHANCEMENT Of RECOUNT TEXT USING ITINERARY AS A MEDIA FOR THE VIII H CLASS IN SEMESTER 2 OF SMP NEGERI 2 MARGOREJO IN ACADEMIC YEAR 2012/2013 - Restiyorini Rahayu (ETERNAL (English Teaching Journal), 2016)
Writing is one of the four language skills that must be mastered students. That writing is an activity that is active and productive and require a systematic way of thinking expressed in written language. The fact that writing is a skill that is considered the most difficult for students in SMP Negeri 2 Margorejo  in the academic year 2012/2013. The ability to write Recount  text students in eight grade students before the study is done on average lower. The purpose of this study was to determine (1) Increasing the student's ability to write text Recount through the use of instructional media. (2) Describe whether itinerary media use can improve the ability to write  recount text for  VIII H class in  semester 2 of SMP Negeri 2 Margorejo in the academic year 2012/2013. Classroom Action Research was conducted in two cycles with the allocation of time each cycle two meetings with study procedures each cycle includes: planning, action, observation and reflection. The results based on preliminary data showed that only 13.3% completeness, once held the act of learning to use media itinerary, the ability of students has increased. When viewed in terms of value, the ability of students has increased sequentially: 57.33, 67.33, and 72.6. Based on these results it can be concluded that the ability to write recount text for VIII H class of SMP Negeri  2 Margorejo  in the academic year 2012/2013 can be enhanced through the use of media itinerary.